Two new synonyms from Tibet (Diptera: Empididae: Clinocerinae) - Sinclair, Bradley J. (Zootaxa, 2017)
The subfamily Clinocerinae (Empididae, Diptera) are aquatic dance flies, most commonly encountered in fast flowing rocky streams and creeks. The adults often rest on emergent rocks and are rather common in temperate regions.